Development of European Power Grid and Its Compatibility with Global Energy Interconnection - Zhengyi Han; Giulia Crespi; Tao Huang; Xin Tan; Zhiyuan Ma; Fang Yang; Han Huang (State Power Economic Research Institute, 2020)
The Global Energy Interconnection (GEI) vision is to enhance the deployment of renewable energy generation on a global scale by building intercontinental power transmission corridors, thereby promoting global decarbonization. Under the premise of a unified electrical market, this paper discusses the compatibility of current development plans of European power grid, proposed by European Network of Transmission System Operators (ENTSO-E), with the long-term GEI scenarios in 2030 and 2050. To fully consider the environmental, social, and political elements in the network expansion, a novel methodological approach is proposed, which combines the techno-economic models with socio-economic decision-making support tools, as the multi-criteria analysis. By this method, the paper computes the optimal power flows in the European network model in the GEI scenarios of 2030 and 2050. The study shows that, at the high load level projected in the GEI scenario, a widely distributed congestion between the Scandinavia area and the European continent would appear, limiting the dispatch of transmission corridors from the Arctic area. The results demonstrate that the planning of GEI will require close coordination and management between transmission system operators (TSO) and institutions in various regions.